Evaluation of Serum IL-17A Levels in Diabetes with Chronic Periodontitis Patients: Pharmaceutical Science-Serum IL-17A in Diabetes - PK, Sasikumar; S Varghese, Sheeja; Sakthisaranya Devi, K; Sekar, Santhosh; Dhivya, S (International Journal of Life Science and Pharma Research, 2022)
IL-17A cytokine is a most studied member of the IL-17 cytokine family and its increased production is associated with autoimmune disease and chronic inflammation including periodontitis. This study was aimed to evaluate the serum IL-17A levels in chronic periodontitis patients with or without diabetes. The study was carried out in 168 subjects and consisted of 6 groups wherein group 1 consisted of 28 Type 1 diabetes patients with periodontitis, group 2 consisted of 28 Type 1 diabetes patients without periodontitis, group 3 consists of 28 Type 2 diabetes patients with periodontitis, group 4 consists of 28 Type 2 diabetes patients without periodontitis, group 5 consists of 28 Non-diabetic patients with chronic periodontitis, group 6 consists of 28 Non-diabetic patients without periodontitis (control group). The Sample of 3 ml venous blood was collected from cubital fossa of each subject and analyzed by using ELISA kit. Overall comparison of IL-17A level in between the groups showed that, there was a significant difference (p value < 0.001) among the groups with highest mean level (5.02±0.45) for group-3 (T2DM+CP) followed by group-5 (only CP) and lowest (1.21±0.49) in group-6 (healthy). The serum IL-17A is significantly high in chronic periodontitis and type 2 diabetes with chronic periodontitis.